DEJAN POPOVIC: UNIFICATION OF TAX LAW IN THE YUGOSLAV STATE: FACULTY OF LAW, UNIVERSITY OF BELGRADE, BELGRADE, 2020, 279 PAGES - Bačanin, Vojislav (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
REVIEW